The Effectiveness of a Wireless Modular Bed Absence Sensor Device for Fall Prevention among Older Inpatients - Subermaniam, Kogilavani; Welfred, Ridgwan; Subramanian, Pathmawathi; Chinna, Karuthan; Ibrahim, Fatimah; Mohktar, Mas S.; Tan, Maw Pin (Frontiers in Public Health, 2017)
Background Falls and fall-related injuries are increasingly serious issues among elderly inpatients due to population aging. The bed-exit alarm has only previously been evaluated in a handful of studies with mixed results. Therefore, we evaluated the effectiveness of a modular bed absence sensor device (M-BAS) in detecting bed exits among older inpatients in a middle income nation in East Asia. Methods Patients aged ≥65 years on an acute geriatric ward who were able to mobilize with or without walking aids and physical assistance were recruited to the study. The total number of alarms and the numbers of true and false alarms were recorded by ward nurses. The M-BAS device is placed across the mattress of all consenting participants. Nurses’ workload was assessed using the National Aeronautics and Space Administration-Task Load Index (NASA-TLX) score, while nurses’ perceptions were surveyed. Results The sensitivity of the M-BAS was 100% with a positive predictive value of 68% and a nuisance alarm rate of 31%. There was a significant reduction in total NASA-TLX workload score (mean difference = 14.34 ± 13.96 SD, p < 0.001) at the end of the intervention period. 83% of the nurses found the device useful for falls prevention, 97% found it user friendly, and 87% would use it in future. Conclusion The M-BAS was able to accurately detect bed absence episodes among geriatric inpatients and alert nurses accordingly. The use of the device significantly reduced the total workload score, while the acceptability of the device was high among our nurses. A larger, cluster randomized study to measure actual falls outcome associated with the use of the device is now indicated.